THE INTROVERTED TYPOLOGY OF THE MAIN CHARACTER IN THE SHORT STORY “LAYSA LAHĀ MAKĀN FĪ AL-JANNAH” BY NAWĀL AL-SA‘DĀWĪ: CARL GUSTAV JUNG’S ANALYTICAL PSYCHOLOGY - Zahrotul Muna; Ali Hasan Al Bahar; Abdur Rosyed; Anisa Faridhotun Nurfatwa; Faika Maida Nabila; Najmatul Auliya (Arabic Literature Department, 2026)
This study aims to analyze the personality typology of the main character, Zainab, in the short story “Laysa Lahā Makān fī al-Jannah” by Nawāl al-Sa‘dāwī using Carl Gustav Jung’s psychoanalytic approach. The short story is selected because it represents women’s inner conflicts resulting from oppression within patriarchal family and social systems. This research employs a descriptive qualitative method using library research techniques, as well as observation and note taking. The data are analyzed based on Jung’s typological concepts, including attitudes (introversion-extraversion) and psychological functions (thinking, feeling, sensing, and intuiting). The findings reveal that the introverted-feeling type is the most dominant aspect, with five identified data, followed by three data of introverted-sensing and two data of introverted-intuition. The dominance of introverted-feeling indicates that Zainab suppresses her desires, emotions, and inner impulses, which she is unable to express openly due to familial pressure and social norms. This condition generates profound inner conflict, causing Zainab’s personality to be shaped more by self-repression than by self-acceptance and self-actualization. This study contributes to enriching the field of literary psychology by applying Jung’s typology to reveal the internalization of patriarchal oppression within the character’s personality structure.